Penerapan Water Tepid Sponge Suhu 37ºC pada Penurunan Suhu Tubuh Anak dengan Hipertermi di Rumah Sakit PKU Muhammadiyah Sukoharjo - Maryamatut Daini Shofiya; Dewi Kartika Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The period of growth and development of children has the potential to get sick more easily. The onset of illness in children is usually followed by several symptoms, one of which is fever. Hyperthermia is a condition where body temperature increases due to an increase in the thermoregulation center in the hypothalamus. Normal temperature in children, where the body's cell tissue works optimally, is between 36.5-37.5ºC. The prevalence of fever cases in children in the 2023 Indonesian Health Survey, with fever in children aged 1-4 years, was 59,235 children. One non-pharmacological therapy that can be used is Water Tepid Sponge. Objective: This study describes the results of measuring body temperature before and after water tepid sponge therapy. Method: This research used a case study of 2 respondents conducted on 31 July – 2 August 2024 for 1 time a day, therapy duration 15 – 30 minutes. Results: the application of water tepid sponge therapy to the two respondents showed comparative results of development before and after therapy in An. Az the temperature drops by 1-1.1º while in An. My body temperature drops by around 1-1.2ºC. Conclusion: The results of the study can be concluded that there was an effect of water tepid sponge therapy on reducing body temperature in both respondents.